Sınıf Iıı Anomalilerin Mandibular Splıntlı Servikal Headgear (Mshg) İle Tedavisi (Vaka Takdimi) - Meliha Rübendüz; Hatice Gökalp; Banu Erdoğan (Galenos Yayinevi, 1996)
It is inevitable to begin CI III treatment in early stages. Although successful results can be achieved by chin-cup therapy, it has some disadvantages; like lesions of the chin and hairy skin, indirect appliance of force resulting a long treatment period and loss of patient cooperation. The aim of this study is to control the posterior rotation of the mandible, beside eliminating the disadvantages of chin-cup and minimizing the treatment period by directing the force to the condyle by the mandibular dental arch. In order to perform this, some of the CI III patients are treated with cervical headgear attached to an acrylic mandibular splint instead of chin-cup and these cases are presented.